The Phenomenon of Touch in Architectural Design and a Field Study on Haptic Mapping - Oktem Erkartal, Pinar; Okem, Hikmet Selim (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2015)
Ocular-centrism is the utilitarian-aesthetic perspective which dominates the perception of spatial quality and architectural success in the West. In locating vision as the dominant discourse in architectural design, this perspective has been criticized for ignoring the physical and psychological relation created between subject and space during the spatial experience, sensual memory, movement and time. The phenomenon of touch, which may be defined as the interaction between architecture and subject dependent on physical and cognitive perception, offers another way of thinking and interpreting architecture, and constitutes an alternative starting point for design. The aim of this study was three-fold: to research and describe the phenomenon of touch in design concepts, to present the effects of hapticity in spatial experience on the user, and to present a visualization study for this phenomenon which is quite challenging to express. For the fieldwork, five buildings designed by Peter Zumthor were chosen. Zumthor stresses the importance of sensation, materiality and atmosphere in the architectural design process. Zumthor's abstract design elements, their use in architectural space and the effect were determined using physical measurement. The findings were represented in haptic mapping. This visualization study consisted of a haptic scatter chart, materiality-affect analysis and sensation analysis and revealed that the phenomenon of touch and concepts identified it such as sensations, influence, materiality and mental associations are not abstract and inaccessible assumptions, but tools which can be included in the architectural design process.
Keywords: Body; hapticity; affect; senses; ocular-centrism; mapping; architectural design; Architecture